Structural and Electrical Studies on Blend Based Mixed Ion- electron Conductor- (PVA: PVK): CH\(_3\)COONH\(_4\): EC System - Agrawal, S. L.; Kumhar, R. P. (Recent Trends in Chemical and Material Sciences Vol. 2, 2021)
The aim of present work is to develop a mixed ion-electron conductor for application as electrode material in electrochemical devices. With this perspective in mind an attempt has been made to prepare and characterize PVA:PVK:CH3COONH4:EC system. XRD, Optical Microscopy, SEM and IR studies assured the formation of polymer blend and composite electrolyte system during structural investigations. Electrochemical measurements reveal improvement in electrochemical window upon addition of ammonium acetate. Ionic charge transport seems to dominate as reflected from I-t measurements. Ionic conductivity of this system is seen to improve by an order of magnitude at room temperature with optimum conductivity (1.27×10-3 S/cm) for 0.4 mole ammonium acetate concentration. Temperature dependent bulk conductivity follows a combination of Arrhenius and VTF behavior. Jonscher Power law seems to be obeyed during a.c. conductivity experiments.